New power-aware routing protocol for mobile ad hoc networks. (25th May 2006) - Djenouri, Djamel; Badache, Nadjib
Since devices used in wireless mobile ad hoc networks are generally supplied with limited autonomous resources, energy conservation is one of the most significant aspects in these networks. Recent studies show that the energy consumed for routing data-packets in mobile ad hoc networks can be significantly reduced compared with the min-hop full-power routing protocols. One of the promising mechanisms proposed in literature to reduce the energy consumption is the transmission power control. In this paper, we define new routing metrics to strike a balance between the required power minimisation and batteries freshness consideration. We also define a new technique which allows the distribution of the routing task over nodes. Using these metrics and techniques we derive from DSR [2] a new power-aware and power-efficient routing protocol, whose performance is analysed by simulation in different situations of mobility and network load.